Influence of study population definition on the effect of age on outcomes after blunt head trauma. (6th December 2018) - Peters, Matthew E.; Hsu, Michael; Rao, Vani; Roy, Durga; Narapareddy, Bharat R.; Bechtold, Kathleen T.; Sair, Haris I.; Van Meter, Timothy E.; Falk, Hayley; Hall, Anna J.; Lyketsos, Constantine G.; Korley, Frederick K.
ABSTRACT: Objectives : The purpose of this study was to assess whether study population definition influences the effect of age on outcomes after blunt head trauma. We hypothesized that examining 'all comers' receiving head computerized tomography after blunt head trauma, fewer older individuals would meet Veterans Administration and Department of Defense (VA/DoD) criteria for traumatic brain injury (TBI), and would, therefore, display better outcomes than younger cohorts. However, restricting to participants meeting VA/DoD criteria for TBI, we hypothesized that older individuals would have worse outcomes. Methods : Data from a recently completed prospective cohort study were analysed with age dichotomized at 65 years. Logistic regression modelling, controlled for potential confounders including head trauma severity, was estimated to measure the effect of age on functional recovery, post-concussion symptoms (PCS), and depressive symptoms at 1-month post-TBI. Results : Fewer older than younger individuals met VA/DoD criteria for TBI. Older individuals had better functional, PCS, and depressive outcomes at 1 month. Restricting to those meeting VA/DoD criteria for TBI, older individuals continued to have better functional and PCS outcomes but had outcomes comparable to younger on depressive symptoms. Conclusions : Contrary to our hypothesis, there was a tendency for older adults to have better outcomes than younger, independent of the diagnostic criteria applied.